The SAGE dictionary of social research methods - Jupp, Victor (London : SAGE, 2006)
Providing up-to-date definitions of all the major concepts and methods encountered when attempting to conduct research in the social field, this text includes techniques for those looking to utilise advanced methods.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: elektronické knihy; electronic books; Social sciences -- Research -- Methodology -- Dictionaries; Culture -- Research -- Methodology -- Dictionaries